An integrated micro data base for tax analysis in Germany - Stefan Bach; Martin Beznoska; Viktor Steiner (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2017)
This paper documents methodology underlying the construction of the integrated data base for our study on 'Wer trägt die Steuerlast in Deutschland? - Verteilungswirkungen des deutschen Steuer- und Transfersystems' (Who bears the tax burden in Germany? - Distributional Analyses of the German tax and transfer system). Financial support from the Hans Böckler Stiftung for the project is gratefully acknowledged. The paper greatly benefited from comments by the members of the scientific advisory council of the project.
Keywords: 330